Bearing Capacity of Strip Footing on Hoek-Brown Rock Mass Subjected to Eccentric and Inclined Loading - Keawsawasvong, Suraparb; Thongchom, Chanachai; Likitlersuang, Suched (Transportation infrastructure geotechnology, 2021)
This paper presents the numerical solutions for the bearing capacity of strip footing under inclined and eccentric loads on rock mass obeying the Hoek-Brown yield criterion. This study applies the lower and upper bound finite element limit analysis to evaluate the numerical solutions. The dimensionless parameters including the geological strength index and the yield parameter of rock as well as the inclined angle and eccentricity of load are considered. The influences of all considered dimensionless parameters on the bearing capacity factors are demonstrated and discussed. Finally, the failure mechanisms of strip footing subjected to inclined and eccentric load on Hoek-Brown rock mass are illustrated to portray the effects of all considered dimensionless parameters.